Spatial dynamics of Maine lobster landings in a changing coastal system - Kim, Jaeheon; Hodgdon, Cameron; Evans, Keith S.; Chen, Yong (Frontiers in Marine Science, 2023)
Continued warming of oceans has caused global shifts in marine species distributions. This can result in changes in the spatial distribution of landings and have distributional impacts on marine resource-dependent communities. We evaluated the spatial dynamics of American lobster (Homarus americanus) landings in coastal Maine, which supports one of the most valuable U.S. fisheries. We coupled a bioclimate envelope model and a generalized additive model to project spatial dynamics of lobster landings under possible climate scenarios. This coupled model was then used to forecast future lobster habitat suitability based on IPCC RCP climate scenarios and predict distributions of fishery landings from this projected lobster habitat suitability. The historical spatial distribution of fishery landings shows the highest proportional landings in Maine’s Southern (southwest) regions. The current distribution of landings shows higher proportional landings in Downeast (northeast) regions with the highest proportional landings in Midcoast (middle) regions. Our results suggest that while the proportion of landings in each zone will remain stable, changes in habitat suitability in the spring and fall will reduce total landings. Future habitat suitability is projected to decrease in spring but increase in fall in Downeast areas. Downeast landings are projected to decrease in the next 30 years, then increase over the subsequent 80 years, depending on RCP scenarios and abundance regimes. Midcoast landings are projected to decrease while Southcoast landings are expected to stay constant. This study develops an approach to link climate change effects to fishery landings. These findings have long-term implications for sustainable, localized management of the Maine lobster fishery in a changing climate.